STUDI PERBANDINGAN PENGGUNAAN PANEL SURYA DENGAN TURBIN ANGIN SEBAGAI SUMBER ENERGI LISTRIK ALTERNATIF DI KAMPUS UNIVERSITAS SEBELAS MARET SURAKARTA - Haziz Muin; Danar Susilo Wijayanto; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
Solar and wind are sources of potential energy that are not widely used. The kinetic energy of wind and thermal energy of solar can be converted into electrical energy source. Both of these energy sources in addition to not polluting are also available in unlimited quantities.This experimental research studying the effect of the slope angle of solar panel to determine the most optimal angle and the feasibility between solar panels and wind turbines in the area of Campus V UNS. Variations of the angle that is used in this research is the angle of 18o; 24o; 30o; and 36o. The measurement is done by measuring the electrical current and the voltage of the electricity produced in solar panels as well as to measure the wind speed as a comparison to find out the electrical power generated in wind turbines. This research was conducted in the area of campus V UNS Pabelan for 30 days.The results showed that the power generated influenced the angle of the slope in the solar panel. The Highest power produced is 41.1 Watt at the intensity of the sunlight 120000 lux on the slope angle of solar panel is 24o, while at the slope angel of solar panels an 18o, 30o, and 36o, in respectively is 37.4; 39.7; and 38.6 Watts. This research states that solar panels produce electrical power more effective and optimal than wind turbines. The highest average of electricity power for 30 days generated by solar panels is 40.19 Watt at 11:20 a.m. while wind turbines produce the highest average of electrical power is 7.88 Watt at 15:40 p.m.